Peran Penting Pendidikan Kewarganegraan dalam Membangun Karakter Siswa Sekolah Menengah Atas (SMA) - Silvia Mahrani; Chiara Fidela Andriani; Mikha Valdo Tonggo Tambunan; Sri Yunita; Dian Kartika Tanjung (Public Service and Governance Journal, 2024)
Civic education is an important element in the character development of high school students. This research investigates the important role of civic education in the character development of high school students. This research uses a literature review method to examine students' character development, particularly civic values, active participation in democratic life, understanding of rights and responsibilities as citizens, and the ability to think and act critically and make responsible decisions. Given global challenges such as extremism, intolerance and social polarization, civic education is becoming increasingly important to develop future generations of leaders committed to tolerance, cooperation and social justice. The purpose of this study is to refine the civic education curriculum and provide appropriate teacher training to ensure that civic education effectively shapes the character of secondary school students and transforms them into active and responsible citizens who care for the community and nation.